2020
DOI: 10.5812/hmj.104835
|View full text |Cite
|
Sign up to set email alerts
|

The Comparison of Serum Vitamin D Level in the Term Neonates With and Without Sepsis in Children Hospital of Bandar Abbas City, Iran From 2016 to 2017

Abstract: Background: Neonatal sepsis is one of the most important causes of an infant’s death, and the identification of its factors has been the subject of many studies. Some new evidence suggested the role of vitamin D in the occurrence of sepsis in infants. Objectives: The aim of this study was to compare the serum levels of vitamin D in neonates with sepsis in the first week of birth and healthy neonates. Methods: This case-control study was performed on 72 term neonates (36 neonates with sepsis as the case and 36 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…An inverse correlation between serum vitamin D levels and the duration of NICU stay was reported in the current study. In contrast, Saadat et al found no correlation between vitamin D levels and the length of hospital stay [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…An inverse correlation between serum vitamin D levels and the duration of NICU stay was reported in the current study. In contrast, Saadat et al found no correlation between vitamin D levels and the length of hospital stay [ 35 ].…”
Section: Discussionmentioning
confidence: 99%